The Trees, My Lungs: Self Psychology and the Natural World at an American Buddhist Center - Capper, Daniel (Zygon, 2014)
This study employs ethnographic field data to trace a dialogue between the self-psychological concept of the self object and experiences regarding the concept of “interbeing” at a Vietnamese Buddhist monastery in the United States. The dialogue develops an understanding of human experiences with the nonhuman natural world which are tensive, liminal, and nondual. From the dialogue I find that the self object concept, when applied to this form of Buddhism, must be inclusive enough to embrace relationships with animals, stones, and other natural forms. The dialogue further delineates a self-psychological methodology for examining religions in their interactions with natural forms.